PENGENDALIAN Meloidogyne hapla PADA TANAMAN TOMAT (Solanum lycopersicum) MENGGUNAKAN AGEN BIOKONTROL JAMUR PEMERANGKAP NEMATODA - Dinna Cinthia Pangestu; Liana Dwi Srihastuti; Eli Masni (Fakultas Biologi | Universitas Jenderal Soedirman, 2023)
AbstraCTRoot-knot nematode is one of the parasitic nematodes on plants that can cause losses in agriculture. Plant parasites are one of the obstacles to increasing the growth of tomato plants (Solanum lycopersicum L.). One of the plant parasites that causes the decrease in tomato plants is the root-knot nematode caused by Meloidygne hapla. Nematodes can infect plants through their roots and can live in tissues causing disruption of root work. The large number of losses in agriculture requires nematode controllers to overcome these nematode attacks. The use of chemical nematicides is widely used by farmers to overcome nematode attacks, but this can have a negative impact on the environment, so alternative nematicides that are environmentally friendly are needed. This study aims to determine the potential ability of the Nematode Trapping Fungus isolated from the Lau Kawar area as a biocontrol agent to press the attack of Meloidogyne hapla on tomato plants. In this study, a completely randomized design was used with 5 treatments namely K(-), K(+), KBF (Carbofuran), LK TS, and LK TK with 3 replications each for 35 days. In vitro assay of nematode-trapping fungi on free-living nematodes was carried out and the test results showed that LK TS isolate had the ability to reduce nematode numbers by 94.5% and LK TK isolate by 86.1% at 24 hours of observation. Based on the bioassay test results, the isolates LK TS and LK TK had the ability to act as biocontrol agents in suppressing the number of vermiform nematodes, root swelling, and root knots in tomato plant roots. LK TS isolate could reduce the number of root nodes by 78% and LK TK isolates by 57.5%. The use of Meloidogyne hapla in research is a nematode that has the lowest infectious power compared to other types of nematodes. There was no significant difference in the effect of nematode infection on the growth of tomato plants.